2016
DOI: 10.1007/s10900-016-0208-4
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Use of South Asian Tobacco Products Among South Asians in New Jersey

Abstract: South Asians are the third largest Asian group in the US and among the fastest growing racial groups in New Jersey. Tobacco consumption among South Asians is characterized by several smoked and smokeless tobacco products indigenous to the Indian subcontinent. However, there is a paucity of research on tobacco use behaviors among South Asians in the US. The goal of this study was to examine the awareness and use of South Asian tobacco products such as bidis, gutkha, paan, paan masala, and zarda as well as other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(61 citation statements)
references
References 15 publications
5
56
0
Order By: Relevance
“…Survey development was informed by review of national and state surveys, as well as the feedback from a series of focus groups [15]. The first draft consisted of ever and current use questions for six “standard” products (i.e., cigarettes, cigars, snuff, chew, pipe, e-cigarettes) and five South Asian products (i.e., bidi, gutka or pan masala, paan or betel quid with tobacco, hookah, supari with tobacco).…”
Section: Methodsmentioning
confidence: 99%
“…Survey development was informed by review of national and state surveys, as well as the feedback from a series of focus groups [15]. The first draft consisted of ever and current use questions for six “standard” products (i.e., cigarettes, cigars, snuff, chew, pipe, e-cigarettes) and five South Asian products (i.e., bidi, gutka or pan masala, paan or betel quid with tobacco, hookah, supari with tobacco).…”
Section: Methodsmentioning
confidence: 99%
“…Four studies also showed that even if respondents were aware of the harmful effects of chewing tobacco and alcohol use, there was scepticism regarding the association of pan/guthka with oral cancer [21,23,26,40]. Similar qualitative findings were reported by Lokhande et al [23], Hrywna et al [40] and Banerjee et al [21] Four studies [26,27,45] found that people perceived betel quid/pan/guthka chewing habit good for their health (12%-43.6%) which makes 'teeth and gum stronger' and believed that it helps them to reduce stress (11.6%-51%), relieve boredom with refreshing feeling (22%-44%). These findings were reiterated by participants in the qualitative studies by Hrywna et al [40] and Banerjee et al [21] :…”
Section: Study Findingsmentioning
confidence: 99%
“…"It has benefit; it can be therapeutic too sometimes," (page 7) [40] ''And there are people who feel good; they think it releases tension/worries. So sometimes I think that having a little can cool your mood if you are feeling angry or annoyed.''…”
Section: Study Findingsmentioning
confidence: 99%
See 2 more Smart Citations